Estudo da cinética de cristalização não-isotérmica de nanocompósitos de PLA/Haloisita - Biazin, Guilherme Gonçalves (2021)
Poly(lactic acid) (PLA) is a biodegradable and biocompatible thermoplastic obtained from renewable sources and with similar properties when compared with petroleum-based polymers. The inclusion of nanoparticles is an alternative that has been shown to be efficient in improving the technological performance of polymeric matrices, producing innovative materials. Halloysite nanotubes (HNT) have great potential for use in PLA nanocomposites, mainly for applications in the biomedical and packaging sectors. Processing conditions (time, temperature, type and deformation rates) and the presence of nanoparticles can affect the PLA crystallization kinetics and, consequently, the product properties (mechanical, thermal, optical, diffusion, biodegradability, etc.). In this work, PLA/HNT nanocomposite filaments were produced by twin-screw extrusion, with different contents of both the PLA D-stereoisomer and HNT, and their influence on thermal, rheological and non-isothermal crystallization kinetics (under quiescent and flow-induced conditions) of PLA was evaluated. TGA, DSC and rheometry analyzes were performed. It was found that the thermal stability of PLA matrices was not influenced by the presence and content of HNT. All nanocomposites showed predominantly viscous behavior, and the increase in the HNT content led to an increase in the storage modulus in oscillatory regime, at low frequencies. Non-isothermal crystallization models, such as Jeziorny, Ozawa and Mo, were applied, showing that the growth of PLA crystals is mostly three-dimensional. It was found that the D-stereoisomer content has a more significant influence on the non-isothermal crystallization kinetics of PLA than the presence or content of HNT.